Kajian Literatur: Pola Asuh Otoritatif Dalam Mendukung Children Well-Being Pada Anak Usia Dini - Ana Marlina; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to examine the role of authoritative parenting in supporting children’s well-being in early childhood. This study employs a literature review approach by analyzing several relevant scientific articles published over the past five years. Data were collected through literature review analysis techniques to identify patterns and key findings from various studies. The results of the study indicate that authoritative parenting, characterized by warmth, responsiveness, and consistent control, makes a significant contribution to children’s well-being. Children raised with this parenting style tend to exhibit better emotional regulation, high self-confidence, positive social interactions, and more optimal psychological development. Furthermore, authoritative parenting also supports the development of independence and resilience in young children. The balance between control and emotional support is a crucial factor in creating an environment that fosters children’s holistic development. Therefore, authoritative parenting is recommended as an effective approach to enhancing children’s well-being in early childhood